Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/apha.13346
|View full text |Cite
|
Sign up to set email alerts
|

Urinary extracellular vesicles: Origin, role as intercellular messengers and biomarkers; efficient sorting and potential treatment options

Abstract: Urinary extracellular vesicles (uEVs) are a heterogenous group of vesicles consisting mainly of microvesicles and exosomes that originate predominantly (99.96%) from kidney, the urinary tract epithelium and the male reproductive tract. Secreted EVs contain molecular cargo from parental cells and provide an attractive source for biomarkers, a potential readout of physiological and pathophysiological mechanisms, and events associated with the urinary system. uEVs are readily enriched and isolated from urine samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 122 publications
(166 reference statements)
2
68
3
Order By: Relevance
“…Exosomes have been shown to carry membrane and cytosolic proteins, mRNAs, micro RNAs, long noncoding RNAs, and other molecules, and these molecule-laden exosomes are considered to play a role in intercellular communication under both physiological and pathological conditions [3][4][5][6]. Accumulative evidence has indicated that the relative abundance of these molecule-bearing urinary exosomes is altered in various kidney diseases [7]. In fact, it has been proposed that several exosome-derived molecules, such as aquaporins (AQPs) [8], miR-125a and miR-351 [6], RNA (MEG3) [9], RNA HOTAIR [4], and fetuin-A, could have potential application as biomarkers [10].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes have been shown to carry membrane and cytosolic proteins, mRNAs, micro RNAs, long noncoding RNAs, and other molecules, and these molecule-laden exosomes are considered to play a role in intercellular communication under both physiological and pathological conditions [3][4][5][6]. Accumulative evidence has indicated that the relative abundance of these molecule-bearing urinary exosomes is altered in various kidney diseases [7]. In fact, it has been proposed that several exosome-derived molecules, such as aquaporins (AQPs) [8], miR-125a and miR-351 [6], RNA (MEG3) [9], RNA HOTAIR [4], and fetuin-A, could have potential application as biomarkers [10].…”
Section: Introductionmentioning
confidence: 99%
“…They are involved in tissue homeostasis maintenance and repair. They may also reflect the pathological state of the releasing cells, making them promising biomarkers of diverse pathologies (Svenningsen et al, 2019). EVs are therefore attractive as biomarkers for diagnosis or prognosis purposes and as therapeutic agents with documented activities related to the parental cell origin.…”
Section: Mesenchymal Stem Cells and Extracellular Vesiclesmentioning
confidence: 99%
“…Plasma EVs are one of the most promising biomarkers for solid organ transplantation, reducing or even obviating the need for renal biopsy (216)(217)(218).…”
Section: Plasma Extracellular Vesiclesmentioning
confidence: 99%